Studi tentang Individualized Education Program (IEP) Bagi Anak Berkebutuhan Khusus (ABK) dalam Pembelajaran PPKn - Zulyan, Zulyan; Yolandari, Joesa; Qurniati, Amnah; Hasibuan, Muslih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to find out the planning and implementation of Individualized Education Program for ABK (visually impaired children) in PPKn learning in SLB N 1 Bengkulu city and how the final results obtained after individualized Educarion. This research is a type of qualitative deriftive research. Data collection tools using interview, observation, and documentation techniques, data analysis techniques used, namely data reduction, data display, verification. The results of this study showed that ppkn learning planning in SLB Negeri 1 Bengkulu city can be carried out well if there is careful planning at every stage. The implementation of PPKn learning in SLB Negeri 1 Bengkulu is the implementation of RPP that has been prepared before. In the process of implementation, students with special needs get the same treatment as students in normal schools generally. In conclusion, the final result of Individualized Educational Program (IEP) for ABK (visually impaired) in PPKn learning, depending on the ability of each child, so that each child has a different end result. Keywords: Children with disabilities, Individualized Education Program (IEP), PPKn Learning